Alia and the story of the rose - Jafri, Adeeba (Goodwood Books; India, 2022)
Alia and the Story of the Rose is a touching tale that follows a young girl named Alia as she embarks on a journey of self-discovery and love, learning valuable lessons about resilience and the beauty of nature through the enchanting story of a rose.